Incidence and type of health care associated injuries among nursing students: an experience in northern Italy - Rubbi, Ivan; Cremonini, Valeria; Butuc, Adriana; Cortini, Carla; Artioli, Giovanna; Bonacaro, Antonio; Pasquinelli, Gianandrea (Acta Biomedica Atenei Parmensis, 2018)
Background and aim of the study: Nursing students are at high risk of injury while on clinical placement. The incidence of injury is three times higher in comparison to other healthcare workers, with a prevalence ranging from 25% up to 33,2%. Lack of knowledge and of experience in delivering nursing care, anxiety and unfamiliarity with the clinical environment all represent risk factors for injury. This study describes the number and type of injuries occurring in an organizational setting where nursing students are trained in simulation laboratories before being exposed to a real clinical environment. Methods: An eight year retrospective observational study (2009 to 2017) was conducted on a non-probabilistic population of 1,403 nursing students from a university in the north of Italy. Incident reports were anonymised and entered in a database. Results: Overall the percentage of students who reported an injury (6,2%) was much lower than the one reported in the literature. Conclusions: The nursing programme curriculum of the above mentioned university consists of frontal lectures, group works, simulation based sessions and supervised clinical practice designed to equip students with all the necessary knowledge and clinical skills to prevent health care injuries. Despite the encouraging results of this study, further actions in order to protect first year students, who are more subject to risk of injuries, are recommended.